HUBUNGAN SANITASI LINGKUNGAN SEKOLAH DASAR DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI KECAMATAN CANDI KABUPATEN SIDOARJO - Nirmala Tri Kartika; Supriyadi Supriyadi; Agung Kurniawan (Preventia : The Indonesian Journal of Public Health, 2016)
Abstract: Dengue hemorrhagic fever (DHF) has increased every year. The DHF case ini Sidoarjo district has increased in 3 years. The case was experienced by many children of primary school age. One factor that can increase the risk of this disease is the environmental sanitation of the school. The study aims to determine the relationship between environmental sanitation of elementary school with the incidence of dengue in the Candi subdistrict, Sidoarjo. This type of research is Analytical Survey. The study population is 29 state elementary schools in Candi subdistrict, Sidoarjo. Samplers using cluster random sampling technique, that obtained 24 schools. Collecting data used for the assessment from Health Office of Sidoarjo District. Analysis of data is used statistical test of Rank Spearman. Based on the study results showed that there is no significant relationship between elementary schools environmental sanitation with the incidence of dengue hemorrhagic fever (0,570> 0,05), with the translation of sub variables studied as follows: there is no significant relationship between the availability of clean water to the incidence of dengue fever dengue (0,293> 0,05), there is no significant relationship between the means of waste disposal with the incidence of dengue hemorrhagic fever (0,729> 0,05), and no significant correlation between the density of mosquito larvae with the incidence of dengue hemorrhagic fever (0,031 <0,05). The conclusion of this study is there is no relationship between the school environmental sanitation, sub variable of water supply and waste disposal facilities with the incidence of dengue fever. There is a relationship between sub variable density of mosquito larvae with.Keywords: school environmental sanitation, dengue fever, SidoarjoAbstrak: Penyakit demam berdarah dengue (DBD) mengalami peningkatan setiap tahunnya. Kabupaten Sidoarjo mengalami peningkatan selama 3 tahun terakhir. Kasus tersebut banyak dialami oleh anak usia sekolah dasar. Salah satu faktor yang dapat meningkatkan resiko penyakit ini ialah sanitasi lingkungan sekolah. Penelitian bertujuan untuk mengetahui hubungan sanitasi lingkungan sekolah dasar dengan kejadian demam berdarah dengue di Kecamatan Candi Kabupaten Sidoarjo. Jenis penelitian yang digunakan adalah Survei Analitik. Populasi penelitian ini adalah semua Sekolah Dasar Negeri di Kecamatan Candi Kabupaten Siodarjo yang berjumlah 29 sekolah, pengambil sampel dengan menggunakan teknik cluster random sampling, diperoleh jumlah sampel, yaitu 24 sekolah. Pengumpulan data menggunakan format penilaian dari Dinas Kesehatan Kabupaten Siodarjo. Analisis data menggunakan uji statistik Rank Spearman. Berdasarkan hasil Penelitian menunjukkan bahwa tidak ada hubungan yang signifikan antara sanitasi lingkungan sekolah dasar dengan kejadian demam berdarah dengue (0,570 > 0,05), dengan penjabaran sub variabel yang diteliti sebagai berikut: tidak ada hubungan yang signifikan antara ketersedian air bersih dengan kejadian demam berdarah dengue (0,293 > 0,05), tidak ada hubungan yang signifikan antara sarana pembuangan sampah dengan kejadian demam berdarah dengue (0,729 > 0,05), dan ada hubungan yang signifikan antara kepadatan jentik nyamuk dengan kejadian demam berdarah dengue (0,031 < 0,05). Kesimpulan dari penelitian ini adalah tidak ada hubungan antara sanitasi lingkungan sekolah, sub variabel ketersediaan air bersih dan sub variabel sarana pembuangan sampah dengan kejadian demam berdarah dengue. Ada hubungan antara sub variabel kepadatan jentik nyamuk dengan kejadian demam berdarah dengue.Kata kunci: sanitasi lingkungan sekolah, demam berdarah dengue, Sidoarjo